2022
DOI: 10.3895/cgt.v15n45.13068
|View full text |Cite
|
Sign up to set email alerts
|

Stereotypes of Brazilian Women’s hypersexuality in European Media: data mining

Abstract: A series of stereotypes about Brazilian women, both older and more recent, are put into circulation in the media by European society. This paper aimed to analyze the European international media discourse with regards to Brazilian women and their different manifestations. We selected 39 texts and use the R program for the quantitative analysis of text mining, the sentiment analysis according to the Bing method and the Bardin qualitative analysis. There were prevalent terms which refer to physical attributes, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 5 publications
(8 reference statements)
0
2
0
Order By: Relevance
“…Portugal. Findings indicated that the stereotypes of hypersexuality and body objectification are still present (Passos et al, 2022). Moreover, when analyzing a television news series broadcasted in Brazil about Brazilian migration to Portugal, Posch and Cabecinhas (2020) found that the migration trajectories highlighted were repetitive and stereotypical, but with an emphasis on elite migrants with a lack of diversity.…”
Section: Cultural Journalism In Brazil and Portugalmentioning
confidence: 99%
See 1 more Smart Citation
“…Portugal. Findings indicated that the stereotypes of hypersexuality and body objectification are still present (Passos et al, 2022). Moreover, when analyzing a television news series broadcasted in Brazil about Brazilian migration to Portugal, Posch and Cabecinhas (2020) found that the migration trajectories highlighted were repetitive and stereotypical, but with an emphasis on elite migrants with a lack of diversity.…”
Section: Cultural Journalism In Brazil and Portugalmentioning
confidence: 99%
“…Moreover, the tendency to generalize and simplify identity processes often leads to social stereotypes (Tajfel, 1963). Although there is a strong relationship between Brazil and Portugal, there is a lack of contemporary studies focused on cross-country media stereotypes, since each study tends to focus on only one national context as the majority is focused on Brazilian stereotypes (Posch & Cabecinhas;Passos et al, 2022).…”
Section: E1546mentioning
confidence: 99%